Theories used to explain care-leavers’ journey out of care: A scoping review - Adrian D. van Breda; Sasambal Reuben (PLoS ONE, 2025)
This study was motivated by Mike Stein’s 2006 critique of care-leaving research as reflecting a ‘poverty of theory’. A scoping review of care-leaving journal articles was conducted for the nine-year period from 2015 to 2023. 252 articles met the inclusion criteria, including that theory must be explicitly mentioned. 133 theories were used across these publications, with resilience theory being used in 24% of articles, life course in 10%, emerging adulthood and attachment in 8% each, social capital in 6% and ecological theory in 4%. Over half of the publications were driven by theory (from conceptualisation, through research design, to interpretation of findings), while a fifth were informed in parts by theory and a quarter alluded only briefly to theory. Three quarters of the articles utilised theory to formulate practice recommendations for care-leaving services. Only two theories could be identified that were constructed to explain care-leaving. Although most theories considered the care-leaver within their social environment, there was little use of structural, systemic, critical and rights-oriented theories. The study concludes that Stein’s original concern has been somewhat addressed over the past several years. Other studies find that around a quarter to half of care-leaving publications use theory. This study confirms that, of those studies that make at least some use of theory, most weave theory firmly into the study and mobilise that theory to make recommendations for practice. Nevertheless, research should become yet more theory-driven, contextual, systemic, rights-oriented and critical theories should be used more frequently, and more needs to be done to build theory for care-leaving.